Utilization of ChatGPT in Supporting the Process of Compiling Student Academic Assignments - Riyanti Riyanti; Lisna Bantulu; Asminar Mokodongan; Tiwuk Herawati; Naurah Nadirah Aisyah (CV. Edujavare Publishing, 2026)
The development of artificial intelligence (AI) technology has brought significant changes to the world of education, particularly in the process of preparing students' academic assignments. One widely utilized innovation is ChatGPT, which can help students generate ideas, develop writing outlines, and improve the quality of academic language and structure. This study aims to analyze the use of ChatGPT in supporting students' academic assignment preparation process and identify the benefits and challenges faced in its use. This study used a qualitative approach with a descriptive research type. Data were collected through interviews, observations, and documentation of students who used ChatGPT in academic activities. Data analysis was conducted using thematic analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. Data validity was maintained through triangulation of sources and methods to ensure the accuracy and credibility of the research results. The results show that the use of ChatGPT has a positive impact on improving the efficiency and quality of academic assignment preparation, especially in terms of idea development, writing structure, and language improvement. However, the use of this technology also poses challenges, such as potential dependency, decreased critical thinking skills, and the risk of violating academic ethics. Therefore, it requires wise and responsible use and support from educational institutions in the form of policies and guidelines for the use of AI.